2020
DOI: 10.3390/ani10081320
|View full text |Cite
|
Sign up to set email alerts
|

Short-, Medium- and Long-Term Metabolic Responses of Adult Meat Ewes Subjected to Nutritional and β-Adrenergic Challenges

Abstract: Shortage and refeeding situations lead to switches in metabolic pathways induced by undernutrition and body energy reserve (BR) replenishment cycles. In a 122-d experiment, 36 adult Merinos d’Arles ewes were chosen and first accustomed to diet ingredients (i.e., wheat straw, pelleted alfalfa and sugar beet pulp) and the facility environment for 22 d. Then, ewes were randomly assigned to one of three “diet challenge” treatments during 50 d, (control, underfed and overfed; 12 ewes each) corresponding to 100%, 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Temporal trends in BW, BCS, and plasma T3 were less sharp. This finding confirms the potential of the aforementioned parameters to be used as reliable biomarkers of the short-term responses of ruminants when facing acute undernutrition events ( Chilliard et al, 1998 ; Ingvarsten and Andersen, 2000 ; González-García et al, 2020a ). Direct effects were not reflected however in the shape of lambs’ BW and ADG curves ( Figure 4 ), demonstrating the capacity of these Romane ewes for responding to the acute CHA without affecting offspring performance in the short-term.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Temporal trends in BW, BCS, and plasma T3 were less sharp. This finding confirms the potential of the aforementioned parameters to be used as reliable biomarkers of the short-term responses of ruminants when facing acute undernutrition events ( Chilliard et al, 1998 ; Ingvarsten and Andersen, 2000 ; González-García et al, 2020a ). Direct effects were not reflected however in the shape of lambs’ BW and ADG curves ( Figure 4 ), demonstrating the capacity of these Romane ewes for responding to the acute CHA without affecting offspring performance in the short-term.…”
Section: Discussionsupporting
confidence: 80%
“…Temporal patterns in the postchallenge period (ability to revert to the initial status) were well described for DMI, DFT, and plasma NEFA, β-OHB, urea, and T3 which showed return to initial plateau around 4 to 5 d after finishing the CHA ( Figures 2 and 3 ; Supplementary Figures S1 to S11 ). The potential of NEFA, β-OHB, and T3 as good biomarkers of BR mobilization-accretion processes in sheep is well known and has been reported previously with meat and dairy ewes at La Fage with different rearing systems ( González-García et al, 2014 , 2015 ) and beyond (e.g., with Mérinos d’Arles meat ewes; González-García et al, 2020a ). Our results are in agreement with the results from Barrio et al (2023) who found DMI and milk yield values at a steady level of 5 d after the end of the CHA in dairy ewes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is a component with a direct impact on the overall resilience of the herd under conditions where fluctuation in feed quantity and quality is one of the main constraints. A similar characterization of BR dynamics has been conducted with Arles Merino ewes subjected to varying energy balances (González-García et al, 2020a).…”
Section: ❚ Body Reserves As a Characteristic Trait In Constrained Con...mentioning
confidence: 99%